A novel curing agent for phthalonitrile monomers: Curing behaviors and properties of the polymer network. (10th February 2016) - Ji, Suchun; Yuan, Ping; Hu, Jianghuai; Sun, Rui; Zeng, Ke; Yang, Gang
Abstract: A novel methyl tetrahydrophthalic anhydride end-capped imide compound (MODA) was firstly used to promote the curing reaction of phthalonitrile monomer 1, 3-bis(3, 4-dicyanophenoxy) (3BOCN). The curing behaviors of 3BOCN/MODA blend were studied by differential scanning calorimetry (DSC) and rheological analysis, which suggested that the blend possessed a wide processing window. IR spectra exhibited no triazine has been formed in the curing process and the nitrile group absorption peak almost disappeared after post-cured, the thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA) revealed that the cured phthalonitrile resins have excellent thermal properties and high glass transition temperature (Tg ). Graphical abstract: Highlights: A novel curing agent was designed and synthesized for phthalonitrile monomer. The new phthalonitrile/curing agent system has great process ability and the cured polymer has excellent thermal properties. No triazine absorption peak was observed in IR spectra of the polymer network. Phthalocyanine and isoindoline were formed during the curing process.